The Effect of Destination Image, Amenities and Prices on Tourists’ Satisfaction: A Study of Visitors of Jatim Park 1, Batu - Denis Twi Febinanda; Peter Remy Yosy Pasla; Uki Yonda Asepta (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2018)
The purpose of this study is to analyze the influence of the destination image, amenities, and prices on the satisfaction of visitors to Jatim Park 1 Batu. The population of this study was visitors to Jatim Park 1 Batu at the time of this study, in April 2018. The sample size used was 100 respondents with the criteria that they had visited Jatim Park 1 and were 20 years old or more. The data were obtained through questionnaires, where tourists accessed via the Google forms application. Data analysis used was a descriptive approach and multiple linear regression statistics. The results show that tourist satisfaction was significantly influenced by prices variable, while the destination image and amenity did not show influence. Thus, Jatim Park 1 manager needs to improve promotion, product development, and quality services to provide a destination image and comfort for tourists.JEL Classification: D22, M31, Z30